ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT BERMASALAH (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Ika Nur Faiza; Nur Diana; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this research is to analyze the influence of Loan to DepositRatio (LDR), Bank Size, and Operating Expenses to Operating Revenues (BOPO) to the Non Performing Loan (NPL) at banking company in IndonesiaStock Exchange (IDX). The independent variables are Loan to Deposit Ratio (LDR), Bank Size and Operating Expenses to Operating Revenues (BOPO)while the dependent variable is the Non Performing Loan (NPL). The samplein this study is an annual report of banking companies in BEI in 2015-2017.The sample is taken by purposive sampling method. The analysis used in thisresearch is multiple linear regression analysis. The result of the researchshows that independent variable that is l Loan to Deposit Ratio (LDR) do nothave significant influence to Non Performing Loan (NPL), while for Bank Sizeand Operating Expenses to Operating Revenues (BOPO) have significantinfluence to. Non Performing Loan (NPL).Keywords: LDR, SIZE, BOPO,